Prediction of carcass main cuts in steers - Jardim, Pedro Osório da Conceição; Ziegler, José Carlos da Silveira; Osório, José Carlos da Silveira (Pesquisa Agropecuaria Brasileira, 2014)
Forty-four carcasses of thirty-five month old steers were measured and evaluated to verify the association among common measurements with weight and percentage of forequarter, side, and saw cuts. Of the variables studied hot carcass weight was the one with best correlation coefficients with forequarter (0.95), side (0.90) and saw cut (0.98). With percentage of forequarter and percentage of saw cut the variables studied did not show significant correlation coefficients, although hot carcass weight did show a highly significant correlation coefficient with percentage of side cut (0,38). Hot carcass weight was the main variable responsible for the variation of forequarter, side, and saw cuts, showing respectively the following determination coefficients: 89.91%, 80.97% and 96.02%. To estimate cuts percentage, variables studied showed determination coefficients lower than 30.93% demonstrating as such not having the best fit to explain the variation in forequarter, side and saw cuts.